El software libre en la gestión documental de bibliotecas, caso práctico Biblioteca Municipal de la ciudad de Guaranda, año 2023 - Alvaro Remigio, Espinoza Toalombo (2024)
The objective of this degree work was a comparative study of free software for the document management of libraries, Case Study Municipal Library of the city of Guaranda, year 2023, to identify the problems and current needs of the Library, the technique of interview and observation was used. The applications of the Integrated Library Management Systems (SIGB) were investigated. These applications are tools specifically designed to facilitate library management and improve the services offered to users. During the research, different types of open source ILMS applications were analyzed, such as Koha, PMB, OpenBiblio, Evergreen, ABCD, KualiOle, Colibri, Invenio, which have proven to be efficient in automating library processes, such as book catalog, lending, user management and materials acquisition. The comparison of these applications provided valuable information to select the most appropriate system according to the needs and requirements of the Municipal Library of Guaranda. The aim is to understand how this technological decision has influenced the efficiency of document management and the improvement of the services offered to the library users.